INTEGRASI PENDIDIKAN ISLAM DAN BUDAYA LOKAL TERHADAP LEBARAN TOPAT DI MASYARAKAT LOMBOK - Heriyadi Heriyadi (LP2M Universitas Ibrahimy, 2025)
This study discusses the integration of Islamic education and local culture in the Lebaran Topat tradition in the Lombok community. Lebaran Topat is a tradition carried out by the Sasak community, especially those in the West Lombok and Central Lombok areas, as a celebration after carrying out the six-day sunnah fast in the month of Syawal. This tradition is not only full of religious nuances, but also thick with local cultural values that have been passed down from generation to generation. The main objective of this study is to find out how Islamic education values are integrated into local cultural practices, and how people interpret these traditions in their social and spiritual lives. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews with 5 religious figures, 10 people from both men and women and 10 young people. The observations made by the researcher are related to the process of lebaran topat starting from making topat in their respective homes, takbiran and roah lebaran in musholla and mosques, pilgrimages to graves and holidays in several tourist attractions such as the beach. This study states that the Lebaran Topat culture in Lombok has several series of activities such as takbiran, making ketupat, dhikr, holidays and grave pilgrimages. The integration of Islamic education and local culture in Ketupat Eid is spiritual education (tarbiyah ruhiyah), faith education (tarbiyah aqadiyyah), physical education (tarbiyah al-badaniyyah), social education (tarbiyah ijtima'iyah) and moral education (tarbiyah akhlaqiyah). Thus, Topat Eid becomes an effective medium in conveying Islamic values contextually, while strengthening the sense of togetherness and local cultural identity. This integration proves that Islamic education does not have to be in conflict with local culture, but can actually run in harmony in forming the character of a religious and cultured society.